ANALISIS EFISIENSI PERDAGANGAN KOMODITAS KEDELAI EDAMAME DI KABUPATEN GOWA - Salmiaty Taty (AkMen JURNAL ILMIAH, 2013)
This study aims to determine: (a) The pattern of institutional and business administration / marketing edamame soybean commodity in order to increase non-oil exports, and (b) structure of edamame soybean commodity markets due to reduced exchange rate.Based on the analysis obtained the following results: (a) Cost is only 45.33 percent of farmers, where farmers’ profits amounted to 31.18 per cent of the FOB price. Reduced acquisition Edamame Soybean farmers due to the instability of the rupiah to the dollar, as well as the influence of global climate change caused a decrease in the quality of Edamame Soybean, (b) obtained the largest profit margin profit margins of exporters with 34.69 percent of the FOB price and traders get the benefit The greatest cost ratio, that is equal to 10.54, and (c) Edamame Soybeans mostly exported, so that with the decline of the rupiah caused Edamame Soybean prices are rising. Edamame Soybean prices in nominal terms on average increased by nearly 100 percent. In 2010 the average per-kg of Rp.9000, up to Rp.16.500, in the year 2011. Edamame Soybean farmers ‘income, using average productivity of the farmers’ income in the year 2011 amounting to Rp.11.070.000,- and in 2012 the income of farmers amounted to Rp.18.810.000,- To develop edamame soybean farming and see the huge role on the economy of edamame soybean Gowa regency, it is necessary to increase the productivity of soybeans Edamame with lending, to manage the more intensive farming and the need for counseling, especially in improving the productivity of soybean edamame